Mobile apps: Pooling resources - Haynes, Joshua (Technical Centre for Agricultural and Rural Cooperation, 2010)
A team of developers has created a single system, called Masawa, to encourage development and delivery of information services to low-cost cell phones via mobile apps. Working with NGOs and local developers, the team will test the system in Kenya in 2011.